ASME 2008 6th International Conference on Fuel Cell Science, Engineering and Technology 2008
DOI: 10.1115/fuelcell2008-65239
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of CO Poisoning of an Air-Breathing High Temperature PEM Fuel Cell Stack

Abstract: In this paper, we experimentally studied an air breathing high temperature PEM fuel cell at steady operating conditions to investigate the effects of CO poisoning at different temperatures ranges between 120°C∼180°C. The effects of changes in temperatures with different amount of CO poisoning on the current-voltage characteristics of the fuel cell are investigated. Experimental data of this type would be very useful to develop design parameters of fuel processor based on reformate hydrocarbons. The high CO tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…While using optimized reformer geometry, at the end of initial reforming process (i.e. before WGS reaction start) we observed that the reformate gas temperature was at Channel length (m) 18 reformate gases need to have temperature at around 800 o K at the end of initial fuel reforming process. In order to comply with these requirements, we used a heat exchanger to bring down the reformate gas temperature from 1115 o K to 800 o K before it entering into the water gas shift reaction zone of the reformer.…”
Section: Reforming Sectionmentioning
confidence: 98%
See 4 more Smart Citations
“…While using optimized reformer geometry, at the end of initial reforming process (i.e. before WGS reaction start) we observed that the reformate gas temperature was at Channel length (m) 18 reformate gases need to have temperature at around 800 o K at the end of initial fuel reforming process. In order to comply with these requirements, we used a heat exchanger to bring down the reformate gas temperature from 1115 o K to 800 o K before it entering into the water gas shift reaction zone of the reformer.…”
Section: Reforming Sectionmentioning
confidence: 98%
“…It is due to the fact that platinum (Pt) catalyst is used in the PEM fuel cell for electro-kinetic reactions to produce useful electric power. CO poison Pt catalyst as per the thermo-absorption and chemisorption properties of Pt [18]. So, it is necessary to make sure that the reformate gas contains very low level of CO in order to avoid Pt poisoning during HTPEMFC stack operation with reformate gas.…”
Section: Reforming Sectionmentioning
confidence: 99%
See 3 more Smart Citations